Transformasi Sistem Pendidikan Formal Pesantren - Ni'am, Shokhibun; Arafah, Nawal Nur (DIMAR: Jurnal Pendidikan Islam, 2024)
This study explores the transformation of formal education in pesantren following the enactment of Law Number 18 of 2019 on Pesantren, which formally integrates pesantren into Indonesia's national education system. As one of Indonesia's oldest educational institutions, pesantren faces significant challenges in aligning its traditional Islamic curriculum with national education standards despite a robust legal framework. This issue is critical since the limited recognition of pesantren diplomas hinders graduates' access to higher education and employment opportunities. However, with the right support and recognition, these graduates have the potential to significantly contribute to the future of Islamic education in Indonesia. Employing a descriptive-qualitative approach with juridical analysis, this research examines the regulatory changes and their implementation in pesantren. The findings reveal that while pesantren have adopted formal education models such as the Mu'adalah curriculum, Pendidikan Diniyah Formal (PDF), and Ma'had Aly, the practical application of these models still faces challenges, particularly in aligning with regulatory standards. The government's immediate and robust support is crucial to address these challenges. It must enhance oversight, provide sustainable funding, and strengthen professional development for pesantren educators. This study underscores the need for inclusive policies that empower pesantren to preserve their Islamic traditions while improving the employability and competitiveness of their graduates. Additionally, it recommends that pesantren adopt adaptive strategies in curriculum design and human resource management. The findings highlight Pesantren's critical role in balancing Islamic educational heritage with modern educational demands, contributing significantly to Indonesia's national education development.